Seeking one's heading through eye movements - Cutting, James E.; Alliprandini, Paula M. Z. [UNESP]; Wang, Ranxiao Frances (Springer Nature, 2000)
A study of eye movements during simulated travel toward a grove of four stationary trees revealed that observers looked most at pairs of trees that converged or decelerated apart. Such pairs specify that one's direction of travel, called heading, is to the outside of the near member of the pair. Observers looked at these trees more than those that accelerated apart; such pairs do not offer trustworthy heading information. Observers also looked at gaps between trees less often when they converged or diverged apart, and heading can never be between such pairs. Heading responses were in accord with eye movements. In general, if observers responded accurately, they had looked at trees that converged or decelerated apart; if they were inaccurate, they had not. Results support the notion that observers seek out their heading through eye movements, saccading to and fixating on the most informative locations in the field of view.
Keywords: adult; depth perception; eye movement; female; human; male; movement perception; orientation; regression analysis; saccadic eye movement; Adult; Eye Movements; Female; Humans; Male; Motion Perception; Orientation; Regression Analysis; Saccades; Space Perception